Pengembangan Budidaya Ikan Koi (Cyprinus Carpio) untuk Masyarakat Sekitar Universitas Terbuka Malang - Kusuma, Jony Puspa; Sulistyowati, Lilik; Ginting, Andi Lopa; Syarif, Moh; Hafa, Fauzi (Jurnal PKM Manajemen Bisnis, 2024)
The community service activity titled "Development of Koi Fish Cultivation (Cyprinus Carpio) for the Community Around Universitas Terbuka Malang" is motivated by the high economic and aesthetic potential of koi fish, which has not been optimally utilized by the local community. Koi fish serve not only as ornamental decorations but also as a potential source of additional income for the community. The aim of this activity is to provide knowledge and skills about koi fish cultivation techniques, as well as to raise community awareness of the economic potential of this venture. The methods used in this program include training and outreach consisting of theory and hands-on practice. This activity involves local communities through socialization, cultivation demonstrations, and assistance in managing koi fish ponds. The results of this community service activity indicate an increase in participants' understanding and skills in koi fish cultivation, along with the establishment of koi cultivation groups in the area. Additionally, participants reported a growing interest in keeping koi fish as a side business.